A study on clinical, immunophenotypic pattern in pediatric acute leukemias in a teaching hospital - Pandian, Guna; Sankarasubramaian, Murugesa Lakshmanan (International Journal of Contemporary Pediatrics, 2018)
Background: Acute leukemia contributes to nearly one third of the pediatric malignancies. For effective management of a curable malignancy, the epidemiology of childhood leukemias and audit of previously treated patients would be required. The objective was to study the clinical and immunophenotypic pattern of acute leukemia in children <12 years of age admitted in a tertiary centre. Methods: Prospective study done on 31 children, diagnosed as leukemia and treated over a period of 3 years in GRH, Madurai. Detailed history analysis, clinical examination, lab investigations including flowcytometry were done. Results: ALL was the most common acute leukemia in children (90.3%). 85.7% were identified as B-cell and 14.3% as T-cell. Of the B-ALL, 87.5% was pre-B, 8.3% pro-B and 4.2% mature B ALL. Myeloid antigen co-expression was seen in 35.7%. Fever was the most common symptom (87%) and hepatosplenomegaly was the most common sign (>90%). Poor outcome was noted in 42.3%. T-cell appeared to have worse prognosis than B-cell but did not retain independent prognostic significance in univariate analysis. Conclusions: B-ALL was more common than T-ALL. Extra medullary organ involvement indicates increased tumor burden and poor outcome. None of the clinical or laboratory parameters appeared to predict poor outcomes in our study and this may be due to small sample size. This study provides an insight into the data regarding the epidemiology, clinicopathologic feature and outcome of acute leukemia in a center with low resource settings.